Correlation of NT-pro BNP Levels with Right Ventricular Parameters in Heart Failure due to Mitral Stenosis - Asrial, An Aldia; Pudjiasti, Anggit (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Mitral stenosis (MS) is a common valvular heart disease that often causes heart failure (HF). The right ventricle (RV) is frequently involved in MS, which contributes to clinical outcomes in patients. NT-pro BNP (N-terminal pro-B-type natriuretic peptide) is a widely used biomarker in the diagnosis and prognosis of heart failure. However, its relationship with RV parameters in patients with HF due to MS remains insufficiently explored. This study aimed to explore the correlation between NT-pro BNP levels and right ventricular parameters in patients with mitral stenosis. Methodology: A total of 40 outpatient subjects with severe MS were included in this study. NT-pro BNP examination was performed using the ELISA method. RV parameter assessment was performed using echocardiography by assessing TAPSE (function) and RV basal diameter (dimension). Results: RV function parameters (TAPSE) and NT-pro BNP showed a significant weak correlation (r=0.324; p=0.041). RV dimension parameters and NT-pro BNP did not show a significant relationship. Patients with RV dysfunction had greater increases in NT-pro BNP levels compared to patients with normal RV function (6441.25±773.18 vs 7671.87±788.72 pg/mL; p=0.172). Applications/Originality/Value: Provides valuable insights into the pathophysiology of right heart involvement in MS and provides clinicians with potential biomarkers for early identification of RV dysfunction in MS patient population.